La@C82 as a spin-active filling of SWCNTs: ESR study of magnetic and photophysical properties - Círić, L; Pierzchala, K; Sienkiewicz, A; Magrez, A; Náfrádi, B; Alexander, D; Warner, J; Shinohara, H; Ruemmeli, M; Pichler, T; Briggs, G; Forró, L (2008)
Electron microscopy (TEM) and electron spin resonance (ESR) were applied to characterize lanthanum metallofullerene (La@C82)-filled peapods. The peapods were prepared by encapsulation of La@C82 in SWCNTs, which were obtained by laser ablation technique in the presence of non-magnetic catalysts Pt : Rh : Re. Empty fullerenes, C60, were used as separators for the spin-active La@C82. TEM analysis confirmed filling of peapods with both C60 and La@C82 molecules. ESR spectra acquired in the temperature range from 5 K to 295 K provided indirect evidence of encapsulation of the spin-active La@C82 in carbon nanotubes and pointed to marked differences in magnetic properties of peapods as a function of the relative concentration of La@C82. Preliminary ESR studies of the photo-physical properties of La@C82 in CS2 revealed that, under illumination with white light, La@C82 neither generated singlet oxygen nor was photoactive against a paramagnetic target, nitroxide radical (TEMPO). © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.